Dinamika Psikologis Korban Sektorsi: Sebuah Kajian Literatur - Istiqomah Yungsiana; Yayi Suryo Prabandari (Asosiasi Psikologi Forensik (Apsifor), 2024)
Sexual extortion or sextortion is a form of sexual violence that occurs in the digital technology realm and is categorised as a type of Online Gender-Based Violence (OGBV). Sextortion refers to exploitative behaviour involving the distribution of sexual images, videos, and other intimate content through deception, coercion, threats, and extortion, compelling victims to provide money or other valuables. This situation places victims under severe psychological pressure, causing significant distress and discomfort. This research aims to examine the psychological impact on sextortion victims. The methodology employs a literature review of various studies, both from Indonesia and internationally, revealing the psychological dynamics of sextortion victims. The literature review findings indicate distinct characteristics between male and female sextortion victims. Male victims are often emotionally manipulated into sending images and subsequently extorted for money, while female victims are more frequently coerced or intimidated into providing sexual content. Victim responses to sextortion comprise five stages: interaction between individual and environment, extortion, assessment and handling, review, and reassessment. Denial, self-awareness, and self-acceptance are crucial processes that sextortion victims must navigate for recovery. Victims suffer significant psychological harm, commonly experiencing panic, shame, fear, worry, sadness, anxiety, humiliation, self-blame, hopelessness, depression, suicidal thoughts, and in extreme cases, suicide attempts.